Sri Lanka and the Covid 19 Crisis: Strategies and Future Challenges - Senevirathna, Asantha (Tribhuvan University Journal, 2020)
COVID-19 pandemic has become a major crisis in 2020. The pandemic has claimed thousands of lives and is spreading a negative economic impact around the global economy. The pandemic has caused a devastating impact on human life in many of the countries without a clear distinction among developed or developing nations. Sri Lanka is facing the heat of the pandemic gradually since January and has taken various measures to combat the situation. The COVID-19 pandemic forwarded a greater challenge to Sri Lanka since the country has faced various disasters in the recent past and question marks remain about the government’s response. The Sri Lankan government response to the current COVID-19 crisis has been largely successful and is ranked among the best responsive countries in the world. This paper discusses Sri Lanka’s strategies in dealing with COVID-19 pandemic and possible future challenges related to the issue.